A mouse model for poliovirus neurovirulence identifies mutations that attenuate the virus for humans. - La Monica, N (1987)
A mutation in the genome of poliovirus type 3 that is known to reduce neurovirulence in humans similarly reduces neurovirulence in mice when incorporated into a mouse-adapted-human poliovirus recombinant. Viral recombinants with a uracil at nucleotide position 472 in the 5'-noncoding regions of their genomes are unable to replicate in the mouse brain. Viral recombinants with a cytosine at this position are neurovirulent in mice. Neurovirulence of poliovirus in mice may therefore prove to be a useful indicator of the genetic stability of new attenuating mutations created by site-directed mutagenesis.